Seeing “Apostates” Clearly: Reconsidering the Legitimacy of Ex-Member Testimony in Documentary Representations of Scientology - Thorn, Michael (Journal of media and religion, 2021)
This article analyzes popular and academic reviews of the book and film Going Clear: Scientology and the Prison of Belief in relation to scholarly debates over the status of “apostate” testimony in the study of New Religious Movements (NRMs). Using a Foucauldian discourse analysis – an examination of contested statements of “truth” – it accounts for the significance of ex-member testimony in recent Scientology exposés and argues the tendency to dismiss such testimony as automatically unreliable needs to be reassessed. Using these exposés and the debate surrounding them as a case study, we can see that considering ex-member testimony as disputed but productive discourse, documentary and journalistic representations of controversial new religions can operate as important sources of information, helping us better map a larger discursive domain wherein allegations of harm intermix with claims of benefit in remarkably complicated ways.